LIMPAPEH RUMAH NAN GADANG IN FILTER PRINT TECHNIQUE GRAPHIC ARTS - Mella Widia Astuti; Irwan Irwan (Universitas Negeri Padang, 2023)
The creation of this final work aims to visualize the philosophy of rumah nan gadang as a depiction of the daily life of Minangkabau women in ancient times into a work of filter-printed (serigraphy) graphic art. The work displays the characteristics of the daily life of women in Minangkabau who are used as the main characters as role models in a community. The author succeeded in realizing this idea into 10 works with the titles: